LANGUAGE, CULTURE AND SOCIETY: A THEORETICAL ANALYSIS OF STUART HALL'S REPRESENTATION AND SIGNIFYING PRACTICES - Mahmud Layan Hutasuhut (BAHAS, 2009)
Language and culture are familiar issues in human life. In fact, some people do not realize that they, as a member of society, produce meanings to their life called 'culture'. Commonly, culture is comprehended as the way of behaving or the way of living. In addition, ordinary people who do not clearly understand this concept think that culture involves traditional performances or some ritual events of a group. Some other people, including the writer, interpret culture as arts creations, such as painting, music and literature. In fact, Hall's concepts on culture have opened up the writer's view on culture. This paper is aimed at exploring Hall's concept of culture in relation to language and society. To make this concept more understandable the writer would like to apply this concept into a specific context in our daily life and the writer's cultural experiences.   Key Words: language, culture, society